1998
DOI: 10.1097/00042560-199805010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Replication by an Aqueous Extract of Spirulina platensis (Arthrospira platensis)

Abstract: An aqueous extract of the blue-green filamentous algae Arthrospira platensis (previously called Spirulina platensis) inhibited HIV-1 replication in human T-cell lines, peripheral blood mononuclear cells (PBMC), and Langerhans cells (LC). Extract concentrations ranging between 0.3 and 1.2 microg/ml reduced viral production by approximately 50% (50% effective concentration [EC50]) in PBMCs. The 50% inhibitory concentration (IC50) of extract for PBMC growth ranged between 0.8 and 3.1 mg/ml. Depending on the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
8

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(91 citation statements)
references
References 19 publications
1
82
0
8
Order By: Relevance
“…our results were also in accordance with those reported by Witvrouw and De Clercq (1997), who emphasized that sulphated polysaccharides were found to be potent and selective inhibitors of HIV-1 replication in cell culture. Moreover, Ayehunine et al (1998) reported that an aqueous extract of S. platensis inhibited HIV-1 replication in human T-cell lines and langerhans cells and their antiviral activity was found in polysaccharides fraction. Our results were confirmed by and coincided with the results reported by Shalaby (2004), where phosphate buffer and water extracts of S. maxima cultivated under different N-conc.…”
Section: Nacl (M)mentioning
confidence: 99%
“…our results were also in accordance with those reported by Witvrouw and De Clercq (1997), who emphasized that sulphated polysaccharides were found to be potent and selective inhibitors of HIV-1 replication in cell culture. Moreover, Ayehunine et al (1998) reported that an aqueous extract of S. platensis inhibited HIV-1 replication in human T-cell lines and langerhans cells and their antiviral activity was found in polysaccharides fraction. Our results were confirmed by and coincided with the results reported by Shalaby (2004), where phosphate buffer and water extracts of S. maxima cultivated under different N-conc.…”
Section: Nacl (M)mentioning
confidence: 99%
“…It is characterized by 70% protein content and the presence of minerals, vitamins, amino acids, essential fatty acids (Mosulishvili et al, 2004), carbohydrates, essential fatty acids, sterols and blue pigments (phytocyanins), which contribute to increasing the protein and iron availability, and a low content of cholesterol and lipids (Jassby, 1983). Spirulina platensis acts as an immunostimulator (Mosulishvili et al, 2004) and has demonstrated anticarcinogenic (Mathew et al, 1995;Mishima et al, 1998) and antiviral effects (Ayehunie et al, 1998). In addition, certain Spirulina subspecies affect the immune system by enhancing phagocytic activity in macrophages (Jassby, 1988) and inhibiting allergic reactions in rodents (Hayashi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In some countries in Asia and Africa where the population daily consumes Spirulina (=Arthrospira), a blue alga, a low incidence of infection with HIV-1 (AIDS) has been noticed (Ayehunie et al, 1998). These studies also showed that these algae have the property of stimulating the immune response (Teas et al, 2004).…”
Section: Seaweed Natural Products: a Brief Presentation Of Promising mentioning
confidence: 99%